Lasers in periodontics - Sugumari Elavarasu; Devisree Naveen; Arthiie Thangavelu (Wolters Kluwer Medknow Publications, 2012)
Laser is one of the most captivating technologies in dental practice since Theodore Maiman in 1960 invented the ruby laser. Lasers in dentistry have revolutionized several areas of treatment in the last three and a half decades of the 20 th century. Introduced as an alternative to mechanical cutting device, laser has now become an instrument of choice in many dental applications. Evidence suggests its use in initial periodontal therapy, surgery, and more recently, its utility in salvaging implant opens up a wide range of applications. More research with better designs are a necessity before lasers can become a part of dental armamentarium. This paper gives an insight to laser in periodontics.